Diferentes estratégias para aplicação de fluido de coite com vazões reduzidas no fresamento do aço VP420 para moldes - Silva, Hélio António da (2014)
The efficiency of cutting fluids can be improved by avoiding its contamination and waste, through the adoption of best practices and techniques for cleaner production, with a consequent reduction of the risks to occupational health and environmental damage. Cutting fluids when handled improperly, eventually reach the soil, air, fauna, flora and water resources, and thus cause serious damage to the environment. For proper management of metalworking fluids, it is necessary to get enough information for users to adopt measures to minimize waste of these fluids. This work shows the research of different strategies for application cutting fluid with flows reduced: low flow - 5 L/h, dripping - 0.20 and 0.32 L/h, MQF (Minimum Fluid Quantity) - 0.025 L/h in end milling operation of steel for molds, VP420. The cutting parameters used were: cutting speed 230 m/min and 185 m/min; feed rate 0.2 mm/rev; radial depth of cut of 9.4 mm and axial depth of cut of 1.0 mm and 0.2 mm for roughing and finishing, respectively. It was adopted as a criterion for end of the tests, the event that occurred first, ie: maximum flank wear equal to 0.3 mm, or a fixed VMR (volume of material removed of the top surface of the material with axial depth of cut of roughing and finishing operations). The maximum flank wear (VBBmax), the surface roughness Rq, cutting forces (force - Fz, torque and power), the characteristics of burrs and chips, obtained during and after removal of the volumes mentioned, were considered to evaluate the performance of the cutting fluids. The results were compared to dry cut, when applying over head flood cooling and in the MQF (Minimum Quantity of Fluid). Method tests have shown that flank wear with the occurrence of chipping. Prevail in all the testes the lower values of surface roughness occurrece when applying cutting fluid at flow rate of 0.20 L/h and cutting speed of 185 m/min, and the MQF 0.025 L/h and cutting speed of 230 m/min. One of the main conclusions is that, in most cases, the application of dripping condition to 0.20 L / h proved to be quite effective for improving the machining process in general.